Mental Health and Public sector Performance: Exploring Root Causes of Public Administrative Dysfunction Beyond Conventional Thinking: A case Study of Public Sector, Lesotho (African Journal of Public Administration & Management, 2026)
Comprehensive Mental Health and Wellness Policy: Introduction of a mental health and wellness policy in the Public Sector, aligned with WHO guidelines for uniform implementation. Training and Awareness: Training of Human Resources personnel and line managers on mental health and wellness programmes for prevention, monitoring, and identifying mental health-related behaviour for referral to the specialists. Community and Digital Solutions: Implement community-based interventions and digital health solutions to improve accessibility in rural areas. E.g, HIV-AIDS community volunteers. Workforce Development: Provide scholarships/sponsorships and career programs to incentivize mental health specialization and expand the workforce.